Economic efficiency analysis of regional rail transport services - Khatamov Ochildi Kurbanovich,; Shakarova Dilfuza Ruzimuratovna, (THE INNOVATION ECONOMY, 2026)
This article analyzes the economic efficiency of regional railway transport services using the example of the Termez railway junction. An author's integral indicator was developed based on the Ryabtsev index.